2008
DOI: 10.1002/jor.20660
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of the insulin‐like growth factor (IGF) binding proteins (IGFBPs) 2 and 3 in articular chondrocytes

Abstract: The insulin-like growth factor (IGF) is a major anabolic regulator in articular cartilage. The IGF-binding proteins (IGFBPs) are increased during osteoarthritis (OA), but the function of the later proteins remains unknown. In general, the IGFBPs are pluripotential effectors capable of IGF regulation and of acting on their own to control key cell functions, including survival and proliferation. The independent functions are often associated with their cell location, and therefore this study explores the distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The production of IGFBP3 in chondrocytes can be increased by the elevated expression of inflammatory cytokines in OA, such as IL1α, TNFα and prostaglandin E2 (28, 29). In the present study, we confirmed the increased expression of IGFBP3 in OA‐like degenerative regions as being reported previously (9, 11) may contribute to neutralisation of IGF1 activity in condylar cartilage. Furthermore, the expression of IGFBP3 also showed gender differences.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The production of IGFBP3 in chondrocytes can be increased by the elevated expression of inflammatory cytokines in OA, such as IL1α, TNFα and prostaglandin E2 (28, 29). In the present study, we confirmed the increased expression of IGFBP3 in OA‐like degenerative regions as being reported previously (9, 11) may contribute to neutralisation of IGF1 activity in condylar cartilage. Furthermore, the expression of IGFBP3 also showed gender differences.…”
Section: Discussionsupporting
confidence: 93%
“…In normal cartilage, IGFBPs extend the half‐life of IGF1, which makes the latter available for receptor binding. However, elevated IGFBP levels, such as the higher levels of IGFBP3 in OA, inhibit the binding of IGF1 to IGFR1, because of the higher affinity of IGF1 to IGFBP than that to IGFR1 (6, 9, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear localization of IGFBP3 is a well-described phenomenon and has been demonstrated in a variety of cellular models (Jaques et al 1997, Li et al 1997, Wraight et al 1998, Liu et al 2000, Sun et al 2008). IGFBP3 possesses a consensus bipartite NLS (Radulescu 1994), and nuclear transport is facilitated by importin-β factor (Schedlich et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“… 17 IGFBP-2 increases proteoglycan production by mediating TGF-β effect on proteoglycan synthesis. 18 Enhanced expression of this factor in MLs and not in spheroids could have connections with the high proliferation rate of cells in ML. On the other hand, spheroids showed enhanced expression of vascular endothelial growth factor (VEGF), CKb 8-1, and macrophage colony–stimulating factor (M-CSF).…”
Section: Discussionmentioning
confidence: 99%